2016
DOI: 10.1016/j.bjid.2015.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Nephrotoxicity during tenofovir treatment: a three-year follow-up study in a Brazilian reference clinic

Abstract: In this study, 275 patients in use of tenofovir were retrospectively followed-up for three years to evaluate risk factors involved in impaired renal function. Analysis of variance (ANOVA) and Tukey's test were used to verify any differences in creatinine levels and estimated clearance at 0, 6, 12, 24 and 36 months, adjusting for the co-variables sex, skin color, age >50 years, arterial hypertension, diabetes and the use of the ritonavir-boosted protease inhibitors (PI/r) lopinavir/r or atazanavir/r. The softwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
1
6
0
1
Order By: Relevance
“…In this study, the incidence of renal dysfunction, defined as > 25% decrement of eGFR using CKD-EPI from the baseline was 9.66 per 100 PYs in HIV-infected patients who started TDF-based ART. Despite the possibility of some differences in the incidence or prevalence of TDF-associated nephrotoxicity according to the measuring methods of eGFR and definition of TDF-associated nephrotoxicity, the results were broadly in line with those of other studies [6,9,15,16]. A retrospective study conducted in Korea showed that the incidence of acute Scr elevation > 1.5 mg/dL regardless of baseline Scr level among patients treated with TDF-containing regimens was 2.8 per 100 PYs [17].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In this study, the incidence of renal dysfunction, defined as > 25% decrement of eGFR using CKD-EPI from the baseline was 9.66 per 100 PYs in HIV-infected patients who started TDF-based ART. Despite the possibility of some differences in the incidence or prevalence of TDF-associated nephrotoxicity according to the measuring methods of eGFR and definition of TDF-associated nephrotoxicity, the results were broadly in line with those of other studies [6,9,15,16]. A retrospective study conducted in Korea showed that the incidence of acute Scr elevation > 1.5 mg/dL regardless of baseline Scr level among patients treated with TDF-containing regimens was 2.8 per 100 PYs [17].…”
Section: Discussionsupporting
confidence: 88%
“…Renal wasting of phosphorus by damaged renal tubules can lead to osteomalacia. Previous studies suggest that older age, advanced HIV disease, low body weight, pre-existing renal impairment, and having comorbidities are risk factors of TDF-associated nephrotoxicity [5-9]. Concomitant use of a ritonavir or cobicistat with TDF was also suggested as a risk factor of renal dysfunction [10-12].…”
Section: Introductionmentioning
confidence: 99%
“…However, we also saw a decline associated with ART containing Abacavir (small number of individuals). Furthermore, in a study from Brazil, the loss in eGFR (CKD-EPI) was approximately 10 ml/min over a period of three years, and male sex, systolic arterial hypertension and age >50 were associated with that decline [ 23 ]. This finding could be of importance in aging African cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Izzedine et al 16 reported that tubular dysfunction or kidney injury occurred approximately 7 months after the start of TDF. In a study of patients that had used TDF for 3 years, eGFR declined by 8% at the end of 2 years and 11% at the end of the third year in comparison with the baseline level 17 . In a metanalysis that involved a total of 17 studies, of which 9 were randomized controlled studies, it was concluded that ART regimens involving TDF led to kidney dysfunction more commonly than those that did not involve TDF 18 .…”
Section: Discussionmentioning
confidence: 99%